Dapatkah Religiusitas Islami Memoderasi Pengaruh Sifat Machiavellian dan Pengetahuan Akuntansi terhadap Persepsi Praktik Creative Accounting? - Dahlia Tri Anggraini; Nur Amalia Aziza (Universitas Muhammadiyah Jakarta, 2022)
Creative accounting basically aims to make financial reports look good and stable according to SAK, currently however, it is used as a manipulation to mislead stakeholders. The manipulation is carried out through numbers in the recording of financial transactions. This self-interest activity tends to benefit one party and mislead another. This study aims to analyze the effect of Machiavellianism and accounting knowledge on the perceptions of creative accounting practice with the moderating role of Islamic religiosity. Using convenience sampling technique, we collect data from three sharia banks that of 30 employees who work in accounting division by distributing questionnaire. We analyze the data with Smart PLS 3 for Windows. This study finds that Machiavellianism and accounting knowledge has a significant positive effect on the perception of creative accounting practice. Meanwhile, Islamic religiosity has no significant negative effect on moderating the influence of Machiavellianism on the perceptions of creative accounting practice, and no significant positive effect on moderating the effect of accounting knowledge on the perceptions of creative accounting practice.